Anxiety's Impact on Mathematics Ability in Tanzanian Secondary School Students: A Singida District Case Study - Francis, John Saqware (International Journal of Scientific Research and Management (IJSRM), 2024)
Professionals in the fields of science, technology, engineering, and mathematics are in greater demand globally. Numerous governmental and commercial organizations have redesigned education and encouraged training to improve workers' and students' math and science proficiency in order to successfully meet this need.  Programs for education and training usually aim to increase participants' understanding of math and science.Tanzania's consistently low math success has alarmed many, including the government, which has led them to investigate potential reasons for the poor performance. It is thought that students' experiences with mathematics anxiety have an impact on their mathematical achievement. This study looked into how secondary school students in Singida district's area performed academically in relation to math anxiety. The study's sample consisted of 1150 students who were selected from twelve secondary schools in the Singida area.To gather data, standardized questionnaires with closed-ended questions were distributed to participants. The study made use of the respondents' terminal exam results in mathematics. To examine the gathered data, both descriptive and inferential statistics were applied. Overall, the findings demonstrated a statistically significant ( 0.025-two tailed) impact of mathematics anxiety on students' academic performance in mathematics. A correlation coefficient, r=0.425 suggests a substantial,  positive association or relationship between the impact of math anxiety and math performance. When all other factors are maintained constant, a regression analysis using the equation